Photocatalytic activities of Fe-Cu/TiO2on the mineralization of oxalic acid and formic acid under visible light irradiation - Kraiwit Apiwong-ngarm (2018)
Pure TiO 2 and (Fe,Cu)-codoped TiO 2 nanoparticles with different nominal doping amounts of Fe and Cu in the range of 0.1-5.0mol% were synthesized by the modified sol-gel method. The samples were characterized in order to obtain the correlation between physicochemical properties and photocatalytic properties by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer, Emmett and Teller (BET) specific surface area, UV-vis diffuse reflectance spectroscopy (UV-vis DRS), X-ray photoelectron spectroscopy (XPS), zeta potential, and inductively coupled plasma (ICP) techniques. Photocatalytic activities of 0.1-5.0mol% (Fe,Cu)-codoped TiO 2 on the mineralization of oxalic acid and formic acid under visible light irradiation were studied and the results were compared to pure TiO 2 and commercial TiO 2 (Degussa P25). The results clearly showed that 0.5mol% (Fe,Cu)-codoped TiO 2 sample exhibited remarkably higher activity than pure TiO 2 . © 2014 Elsevier B.V.